Lean Software Development for Reducing Bureaucratic Waste in Internship Administration - Nasir Zumali; Hilyah Magdalena (Politeknik Ganesha Medan, 2026)
Government internship administration in Indonesia remains heavily reliant on manual procedures, causing substantial operational waste. While prior studies have applied agile methods to digitize similar workflows, none have quantitatively measured bureaucratic waste reduction using inferential statistical validation. This study contributes a novel integration of Lean Software Development with Value Stream Mapping and inferential statistics to empirically validate waste elimination in public sector internship administration. A mixed-method explanatory sequential design was employed. First, Value Stream Mapping quantified lead time and cycle time on 30 paired internship applications. A web-based system was then developed using Lean Software Development principles. Functional validity was verified through Black Box testing with 50 test cases, and user satisfaction was assessed using the System Usability Scale on 30 respondents. The Shapiro-Wilk normality test confirmed non-normal data distribution, justifying the Wilcoxon Signed-Rank Test for hypothesis testing. Results demonstrated complete functional validity, a 97.5% reduction in lead time from 72.5 to 1.8 hours (Z=-4.782, p<0.001, r=0.87), a 90.9% reduction in cycle time from 25.4 to 2.3 minutes (Z=-4.801, p<0.001, r=0.88), and an excellent System Usability Scale score of 82.5. These findings provide empirical evidence that integrating Lean principles with robust statistical validation offers a replicable framework for quantitatively measuring bureaucratic efficiency gains, advancing beyond descriptive case studies in digital governance research.